Aspects of the phonology of labial-velar stops - Michael Cahill (LibraryPress@UF, 1999)
Phonological patterns of labial-velar stops [kp, gb] are distinctively different from other consonants in their distribution and participation in phonological processes. A summary of cross-linguistic (> 80 languages) patterns of labial-velars includes phonemic inventories, co-occurrence patterns with vowels and consonants, and phonological processes that involve labial-velars. To explain these patterns, phonetic distinctives of labial-velars are presented, as well as the historical development of labial-velars. Feature Geometry and Articulatory Phonology are shown to account for some patterns. The conclusion drawn is that some patterns are best explained by diachronic factors, and there is no single current phonological theory that adequately accounts for all the other patterns.